2007
DOI: 10.1158/1078-0432.ccr-07-0822
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Estrogen Receptor-α at Ser167 Is Indicative of Longer Disease-Free and Overall Survival in Breast Cancer Patients

Abstract: Purpose: Ser 167 was first identified as a major phosphorylation site of the estrogen receptor -a (ER) positive in the MCF7 breast cancer cell line. Subsequent studies have shown that Ser 167 phosphorylation is important in the regulation of ER activity and have identified p90RSK and AKT as protein kinases that phosphorylate Ser 167. The purpose of this study was to determine the importance of Ser 167 phosphorylation in breast cancer progression. Experimental Design: Immunohistochemical staining of primary bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 55 publications
(49 reference statements)
9
83
1
Order By: Relevance
“…In keeping with this hypothesis, expression of ER␣ phosphorylated at the AKT phosphorylation site S167 is associated with a good prognosis in breast cancer: pAKT levels in this patient cohort positively correlated with S167 phosphorylation. 53 Additionally, an AKT1_E17K mutation, which correlates with an increase in AKT phosphorylation, is observed exclusively in ER␣ϩ/PRϩ tumors and is associated with favorable prognosis. 54 Furthermore, during the revision of this manuscript, Kalinsky and colleagues showed that a PIK3CA H1047R mutation, which in cell-based assays cause robust AKT activation, is associated with ER␣-positivity, node-negativity, HER2-negativity, and improved long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this hypothesis, expression of ER␣ phosphorylated at the AKT phosphorylation site S167 is associated with a good prognosis in breast cancer: pAKT levels in this patient cohort positively correlated with S167 phosphorylation. 53 Additionally, an AKT1_E17K mutation, which correlates with an increase in AKT phosphorylation, is observed exclusively in ER␣ϩ/PRϩ tumors and is associated with favorable prognosis. 54 Furthermore, during the revision of this manuscript, Kalinsky and colleagues showed that a PIK3CA H1047R mutation, which in cell-based assays cause robust AKT activation, is associated with ER␣-positivity, node-negativity, HER2-negativity, and improved long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…S6K1 has earlier been implicated in the regulation of ER signaling by phosphorylating ERα-Ser 167, leading to increased ER transcriptional activity and cell growth in vitro [40]. In addition, phosphorylation of ERα-Ser 167 has been associated with better response to tamoxifen [41,42], and a similar role for S6K2 in ER phosphorylation may be conceivable. The proline-rich motif found in S6K2 may support this speculation, since a proline rich, SH3 binding domain in certain ER coactivators have been shown essential for their function and interactions with ERα [43].…”
Section: Treatment Predictionmentioning
confidence: 99%
“…Roughly, 70% of human breast tumors express significant levels of estrogen receptor alpha (ERα) (1), making antiestrogen therapy an important therapeutic modality in breast cancer treatment (2)(3)(4) There is extensive data supporting various correlations between ERα phosphorylation patterns and sensitivity to antiestrogen therapy and clinical indicators of treatment response (delayed disease progression/ improved survival) (6)(7)(8)(9)(10). ERα phosphorylation of serine residues in the activation domain function 1 (AF-1) leads to enhanced ERα-driven transcription via modulation of coactivators recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapy resistant ERα is associated with high Ser 118 phosphorylation which is estradiol independent and has been linked to MAPK activation via Her2-MAPK pathwaydriven phosphorylation of AIB1 (amplified in breast cancer 1) which is a coactivator of ERα and, when overexpressed, is involved in both de novo and acquired tamoxifen resistance (12)(13)(14). High ERα Ser167 phosphorylation, which seems to be estrogen dependent (7)(8)(9)15), has been linked to better response to endocrine therapy and improved survival. Furthermore, recent data suggests that when various Ser118 and Ser167 phosphorylation states are compared, a combination phenotype with low Ser118 and high Ser167 phosphorylation correlates with best clinical indicators of response (disease free survival and overall survival) (7).…”
Section: Introductionmentioning
confidence: 99%